Construction of a model for the system that controls how educational institutions are provided with material resources in a multi-level management structure - Utyubayev, Yelnar; Shaporeva, Anna (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates a system that provides educational institutions with material resources within a multi-level governance structure. The task addressed relates to the lack of a hierarchical, risk-based model for assessing how educational institutions are provided with material resources that would allow for the aggregation of indicators at various management levels. Such a model should account for the standard equipment requirements, equipment operational risks, as well as the hierarchical aggregation of indicators at the educational institution, municipal, and regional levels. The result of this work is the devised integrated resource provision indicator that takes into account the standard resource sufficiency, equipment depreciation, failure probability, as well as exceedance of the standard service life. A mechanism for aggregating indicators at the educational institution, municipal, and regional levels has been designed. The model was tested using synthetic data. At the educational institution level, a significant differentiation in the resource provision index was observed, ranging from 0.492 to 0.782. At the municipal level, the lowest value was 0.580 due to the influence of the school with the lowest resource provision index. The regional index value was obtained at 0.663. Its decline was influenced by the uneven distribution of pupils across schools in the region and the significant risk of infrastructure degradation at one school. The results have confirmed the model’s sensitivity to risk components and the capability to identify regional imbalances in provision. The model built can be used to monitor the state of educational infrastructure and support management decision-making